Controversial Treatments of Shoulder Injuries - Nichols, Emma Hitt (MD Conference Express, 2014)
Repair of shoulder injuries is rising and multiple treatment options exist. Multiple factors are involved in satisfactory healing of the rotator cuff including the quality of the tendon and muscle, repair biomechanics, and patient quality. This article discusses patch reinforcement in the repair of rotator cuffs, as well as about biologics that are available for rotator cuff repair, treating fractures with reverse arthroplasty, and indications for hemiarthroplasty and total shoulder replacement.